2022
DOI: 10.18421/tem111-14
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Scientific Results into Educational Materials - Added Value of a Research Project

Abstract: In recent years, there has clearly been a trend towards widespread dissemination of scientific results and achievements by sharing them in the form of educational materials. The application of the results of a research project in the education and knowledge development of students, young researchers and scientists, brings an added value to the outcomes of the scientific project. This work aims at contributing to the global process of free access to scientific materials by sharing the experience of a research g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…and M.Sc. study programs [2,3]. In an extensive review conducted by Adnan and Xiao, which analyzed 156 research articles across six health disciplines, it was revealed that 35% of studies employed 3D digital printing tools, particularly in educational activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…and M.Sc. study programs [2,3]. In an extensive review conducted by Adnan and Xiao, which analyzed 156 research articles across six health disciplines, it was revealed that 35% of studies employed 3D digital printing tools, particularly in educational activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance teaching approaches and foster the acquisition of knowledge and skills, a modernization approach in training programs involves the utilization of realistic anatomical models through the implementation of 3D printing technologies. They offer possibilities for printing anatomical objects for medical education as well as to introduce the 3D printers as a core tool in basic and advanced elective courses in BSc and MSc study programs [14,15]. The source of the 3D printing model is the digital model that may be created from medical simulators or patient specific data [16,17].…”
Section: Introductionmentioning
confidence: 99%